Influence of parity on fetal hemodynamics and amniotic fluid volume at term. (December 2014) - Prior, T.; Mullins, E.; Bennett, P.; Kumar, S.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 44: 631–631